Evaluation of Finger Blood Flow with Tc-99m MDP (methylene diphosphonate) - Bang, Shin Ho (Korean J Intern Med, 1992)
BACKGROUND: A variety of methods were used to establish objective diagnostic criteria of Raynaud’s phenomenon. We intended to introduce another method, using radionuclide (Tc-99m methylene diphosphonate) scintigraphy, which is more objective, simple and economical than the past methods. METHODS: The finger blood flow with radionuclide scintigraphy was evaluated in 10 patients of Raynaud’s syndrome, 12 patients of connective disease without Raynaud’s symptoms, and 20 normal persons. After immersing one hand in ice water (4°C) for 30 seconds, the hand was exposed to 22°C room air for 15 minutes, and then the patients received the intravenous (IV) bolus of 20 μCi of Tc-99m methylene diphosphonate (MDP). At the same time, scintigraphic image of both hands started with the region of interest, including the second, third, fourth and fifth fingers distal to the metacarpophalangeal (MCP) joints. Computer recording of the counts in the region of interest every 2 seconds for 310 seconds was started on IV bolus injection. RESULTS: The 310 seconds cumulative digital blood flow ratio of cold exposed hand to room air exposed hand was significantly lower in Raynaud’s group (p<0.001), and the ratio of initial slope of activity curve was also lower in the Raynaud’s group (p<0.001). Of the 8 patients showing Raynaud’s syndrome, 4 patients of scleroderma and 1 patient of multiple myeloma showed no improvement of finger blood flow in the cold exposed hand after 2 weeks of pharmacological therapy, but 1 patient of mixed connective tissue disease, 1 patient of Behcet’s syndrome and 1 patient of SLE showed much improved finger blood flow after combined administration of vasodilator, calcium channel blockers and anti-platelet drugs. CONCLUSIONS: The evaluation of finger blood flow with (99m)Tc-MDP could be considered to be one of the simple, economical and new methods that can be used in the follow-up, objective assessment of therapeutic effect, and giving an aid in the study of the pathophysiology of the Raynaud’s phenomenon.